Analisis Yuridis Penanganan Perkara Tindak Pidana Pungutan Liar Oleh Penyidik Kepolisian - Dewi Khartika Siburian; Muhammad Hizbullah (Albayan Journal of Islam and Muslim Societies, 2024)
This research examines the role and position of police investigators in handling extortion cases, the forms of law enforcement undertaken, as well as the obstacles and efforts encountered. The police hold an ambivalent position in the context of extortion: as law enforcers obligated to eradicate illegal levies, while also potentially being perpetrators themselves. This study employs a normative juridical method with a descriptive-analytical approach. The findings reveal that the legal basis for handling extortion lies within the Indonesian Penal Code (KUHP), Law Number 20 of 2001 concerning Corruption, and Presidential Regulation Number 87 of 2016 concerning the Saber Pungli Task Force. The main obstacles in eradicating extortion include weak socialization, lack of internal supervision, and low legal awareness among society. The study highlights the necessity of strengthening internal police oversight and enhancing inter-agency coordination to ensure that anti-extortion efforts are not merely repressive but also preventive. The novelty of this research lies in its comprehensive legal analysis of the role of police investigators within the Indonesian legal framework and its contribution to strengthening the integrity of law enforcement institutions.